Single-case disconnectome lesion-symptom mapping: Identifying two subtypes of limb apraxia. (6th June 2022) - Metzgar, Rachel; Stoll, Harrison; Grafton, Scott T.; Buxbaum, Laurel J.; Garcea, Frank E.
Abstract: Influential theories of skilled action posit that distinct cognitive mechanisms and neuroanatomic substrates support meaningless gesture imitation and tool use pantomiming, and poor performance on these tasks are hallmarks of limb apraxia. Yet prior research has primarily investigated brain-behavior relations at the group level; thus, it is unclear whether we can identify individuals with isolated impairments in meaningless gesture imitation or tool use pantomiming whose performance is associated with a distinct neuroanatomic lesion profile. The goal of this study was to test the hypothesis that individuals with disproportionately worse performance in meaningless gesture imitation would exhibit cortical damage and white matter disconnection in left fronto-parietal brain regions, whereas individuals with disproportionately worse performance in tool use pantomiming would exhibit cortical damage and white matter disconnection in left temporo-parietal brain regions. Fifty-eight participants who experienced a left cerebrovascular accident took part in a meaningless gesture imitation task, a tool use pantomiming task, and a T1 structural MRI. Two participants were identified who had relatively small lesions and disproportionate impairments on one task relative to the other, as well as below-control-level performance on one task and not the other. Using these criteria, one participant was disproportionately impaired at meaningless gesture imitation, and the other participant was disproportionately impaired at pantomiming tool use. Graph theoretic analysis of each participant's structural disconnectome demonstrated that disproportionately worse meaningless gesture imitation performance was associated with disconnection among the left inferior parietal lobule, the left superior parietal lobule, and the left middle and superior frontal gyri, whereas disproportionately worse tool use pantomiming performance was associated with disconnection between left temporal and parietal regions. Our results demonstrate that relatively focal lesions to specific portions of the Tool Use Network can be associated with distinct limb apraxia subtypes. Highlights: Distinct subtypes of apraxia are supported by distinct neuroanatomic substrates. Fronto-parietal lesions are associated with meaningless imitation deficits. Temporo-parietal lesions are associated with tool use pantomiming deficits. Structural connectivity among cortical areas supports a distributed praxis system.